2003
DOI: 10.1177/00207640030493008
|View full text |Cite
|
Sign up to set email alerts
|

Women with Schizophrenia and Broken Marriages - Doubly Disadvantaged? Part I: Patient Perspective

Abstract: This is a qualitative study of 76 women with schizophrenia whose marriages had broken. The sample was drawn from three different centres. Using qualitative methods of exploration, information regarding their illness, the marriage and its separation and the various consequences of this event was gathered. Many of them had not separated legally and were not receiving any maintenance from their husbands. Their concerns centred around their future, the fact they would be a burden to their ageing parents and in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 8 publications
3
58
0
Order By: Relevance
“…The association between schizophrenia and low socio-economic status can be partly explained by the "social drift hypothesis", i.e., schizophrenia patients fail to cope with the social and occupational demands leading to a downward move to lower socio-economic levels Karno and Norquist, 1995). Unmarried status was significantly associated with risk of schizophrenia in this study, which is also in agreement with earlier studies (Agerbo et al, 2004;Lin, 2002;Thara et al, 2003;Thara and Srinivasan, 1997). Some authors have concluded that being single or divorced may increase the risk of schizophrenia (Agerbo et al, 2004;Lin, 2002).…”
Section: Socio-demographic Correlates Of Schizophreniasupporting
confidence: 93%
“…The association between schizophrenia and low socio-economic status can be partly explained by the "social drift hypothesis", i.e., schizophrenia patients fail to cope with the social and occupational demands leading to a downward move to lower socio-economic levels Karno and Norquist, 1995). Unmarried status was significantly associated with risk of schizophrenia in this study, which is also in agreement with earlier studies (Agerbo et al, 2004;Lin, 2002;Thara et al, 2003;Thara and Srinivasan, 1997). Some authors have concluded that being single or divorced may increase the risk of schizophrenia (Agerbo et al, 2004;Lin, 2002).…”
Section: Socio-demographic Correlates Of Schizophreniasupporting
confidence: 93%
“…Studies have reported that women and children with psychotic disorders in developing countries may be vulnerable and have considerable social disadvantages such as having difficulty in getting married, being thrown out of the house by the in-laws due to mental illness and the fear of being a burden to their parents. 16,17 The findings indicate that stigma is pervasive irrespective of the educational status or rank.…”
Section: Resultsmentioning
confidence: 94%
“…First, SMI limits women from fulfilling family and social roles, leading to these women being considered a burden for the family. This is true despite studies such as the Indian study of women with schizophrenia abandoned by their husbands who expressed the desire to work to support themselves 58. Second, traditional beliefs (punishment for previous lives, evil eye/curse), as well as negative lay attitudes on causes and behaviours, lead to increased discrimination of and sometimes violence against SMIs, particularly for women 59…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the PSMI, stigma and discrimination have a negative effect on family members and caregivers who often feel ashamed, embarrassed or unable to cope with the stigma 58 63–67. While there have been campaigns and policies to address discrimination against SC/ST/OBC and women in India, no large-scale awareness campaign has ever addressed the prejudice and discrimination faced by PSMIs.…”
Section: Discussionmentioning
confidence: 99%